(untitled) (Research, Society and Development, 2022)
The use of computer systems allows professionals to continue education, study and virtual surgical planning, and obtain physical objects directly from the generated data. The images obtained from computed tomography can be manipulated using free software. Rapid prototyping is widely used in Oral and Maxillofacial Surgery and Traumatology, allowing for increased surgical predictability, reducing the time associated with the procedure and consequently resulting in lower patient morbidity, lowering the costs associated with health care. This paper describes the protocol for the use of rapid prototyping techniques applied to patients with treatment needs in the specialty of Oral and Maxillofacial Surgery and Traumatology, at the tertiary level of health care, linked to the Unified Health System, in a teaching hospital from the south of Brazil. It also explores parameters related to image acquisition by computed tomography, structural characteristics of the software used, equipment and dimensional quality criteria of the materials used. The adoption of these technologies improves the quality of care and must be encouraged within the Unified Health System.